2016
DOI: 10.1186/s12957-016-0900-y
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Decreased microRNA-452 expression and its prognostic significance in human osteosarcoma

Abstract: BackgroundMicroRNA-452 (miR-452) was previously reported to be dysregulated in several types of human cancers and involved in tumor progression. The aim of this study was to investigate the clinical significance and prognostic value of miR-452 expression in human osteosarcoma.MethodsThe expression of miR-452 was detected in 95 pairs of osteosarcoma specimens and adjacent noncancerous bone tissues using quantitative RT-PCR (qRT-PCR) assay. Then, the association of miR-452 levels with clinicopathological feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
1
12
0
2
Order By: Relevance
“…After screening the titles and abstracts, 63 references reported on the correlation between miRNA expression and either patient survival or disease recurrence in osteosarcoma. Among these, 35 studies reported at least one unique miRNA, so a pooled analysis would not be possible [ 6 40 ]. Finally, 24 articles encompassing 30 studies were include in the meta-analysis [ 3 5 , 41 – 61 ] (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…After screening the titles and abstracts, 63 references reported on the correlation between miRNA expression and either patient survival or disease recurrence in osteosarcoma. Among these, 35 studies reported at least one unique miRNA, so a pooled analysis would not be possible [ 6 40 ]. Finally, 24 articles encompassing 30 studies were include in the meta-analysis [ 3 5 , 41 – 61 ] (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Clinically, OS presents local pain and swelling with occasional joint dysfunction. 12 As our knowledge of the molecular pathogenesis of OS expands, potential therapeutic targets are being identified. In addition to surgery, chemotherapy, and radiotherapy, the comprehensive treatment of OS also includes molecular targeted therapy, immunotherapy, gene therapy, embolization, radiofrequency ablation, and stem cell therapy.…”
Section: Discussionmentioning
confidence: 99%
“…11 Current treatments for OS are associated with significant morbidity, and a period of there is a real need to optimize current treatment strategies and to develop novel approaches for treating OS. 12 As our knowledge of the molecular pathogenesis of OS expands, potential therapeutic targets are being identified. 13 Through analysis by GEO database and R2 chip analysis platform, we obtained three genes (CLEC5A, ALOX5AP, and RNASE3) associated with OS metastasis.…”
Section: Os Derives From Primitive Bone-forming Mesenchymal Cells and Ismentioning
confidence: 99%
“…Another study showed that ectopic expression of miR-212 induces apoptotic death in T-ALL cells 9. Downregulation of miR-452 occurs in several cancer types such as non-small cell lung cancer (NSCLC)10 and osteosarcoma11 and shows a poor prognostic impact on patient survival. In vitro studies demonstrated that miR-452 exhibits anti-invasive activity in NSCLC12 and prostate cancer 13.…”
Section: Introductionmentioning
confidence: 99%